Voluntary giving and economic growth: Time series evidence for the US - Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This study analyzes the sensitivity of US giving to both business cycle fluctuations and trend growth. With tax revenues as a point of reference, US giving constitutes a relatively stable source of revenue. Total giving is characterized by a business cycle volatility which is comparable to the moderate one of indirect taxes. However, this overall finding is composed of the respective sub-components' very different short-run GDP-elasticities. Individual and, to an even larger extent, corporate giving is quite sensitive to cyclical fluctuations. By contrast, foundation giving and charitable bequests tend to stabilize total giving over the business cycle. The macro estimates for the income elasticities lie in the upper band of the well researched micro-estimates. This is consistent with a social multiplier view according to which individual giving is mutually reinforcing.
Keywords: H27; H41; C22; 330; charitable giving; social multiplier; error-correction-model; Spende; Wirtschaftswachstum; Konjunktur; Schätzung; Deutschland